La rêverie d’essor ou comment Marcelle, ne pouvant se mouiller les pieds dans la mer, y plonge ses songes - TAUVERON, Catherine (Ondina - Ondine, 2019)
Ne te mouille pas les pieds, Marcelle (Come away from the water, Shirley) by John Burningham is a picture book that, in its time (1977), broke the bounds of convention1) by telling simultaneously two stories or showing two parallel worlds on pages opposite one another : on the left-hand pages, the « real » world of a family trip to the sea-side, on the right-hand pages, the imaginary world of the little girl Marcelle (Shirley) who goes off maternal injunctions on a daydream adventure with pirates and hidden treasure and crowns herself queen, 2) by immersing the reader in the very heart of a childish inner world, given naked, without comment or adult supervision; 3) by delivering to the children a message that will be called libertarian. We study the cause-and-effect relationships of the two parallel worlds, their mode of construction, graphic and narratological, the gestation of the childhood reverie, its meaning as well as that of the imaginary cartography that accompanies it. Key words: juxtaposed worlds in different spaces / times, dive into childish subconsciousness, compensatory daydream, glorifying maritime adventure